2021
DOI: 10.1093/hropen/hoab011
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Receptivity Analysis (ERA): data versus opinions

Abstract: This article summarises and contextualises the accumulated basic and clinical data on the ERA test and addresses specific comments and opinions presented by the opponent as part of an invited debate. Progress in medicine depends on new technologies and concepts that translate to practice to solve long-standing problems. In a key example, combining RNA sequencing data (transcriptomics) with artificial intelligence (AI) led to a clinical revolution in personalising disease diagnosis and fostered the concept of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 84 publications
3
37
0
Order By: Relevance
“…More importantly, ERA results remain reproducible in the same individual across multiple menstrual cycles (from 29 through 40 months) as long as the body mass index (BMI), endometrial thickness, and treatment regimens are not changed during this period [ 17 ]. Previous studies have shown the effectiveness of ERA for the prediction of the WOI, and the ERA test was identified as an effective and reproducible approach to guiding pET [ 18 22 ]; however, the efficacy of such a tool for pET in Chinese women requires further investigation [ 23 ]. Therefore, this study aimed to compare the effectiveness of ERA-guided pET with conventional frozen embryo transfer (FET) in 281 Chinese women with RIF.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, ERA results remain reproducible in the same individual across multiple menstrual cycles (from 29 through 40 months) as long as the body mass index (BMI), endometrial thickness, and treatment regimens are not changed during this period [ 17 ]. Previous studies have shown the effectiveness of ERA for the prediction of the WOI, and the ERA test was identified as an effective and reproducible approach to guiding pET [ 18 22 ]; however, the efficacy of such a tool for pET in Chinese women requires further investigation [ 23 ]. Therefore, this study aimed to compare the effectiveness of ERA-guided pET with conventional frozen embryo transfer (FET) in 281 Chinese women with RIF.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these methods of assessing the temporal boundaries of the physiologic WOI lack precision and objectivity ( Lessey, 2011 ; He et al, 2021 ). In an estimated 30% of IVF cycles where transfer of embryo is conducted blindly, displacement of WOI happens and embryo-endometrial synchrony is not attained ( Ruiz-Alonso et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been carried out to explore the clinical utility of pET guided by the ERA on IVF/ICSI outcomes, and to discover the rate of WOI displacement in different infertile cohort, demonstrating contradictory or conflicting results. Because of skyrocketed utilization of the ERA and the high cost for conducting ERA ( Ruiz-Alonso et al, 2021 ), the present meta-analysis aimed to determine if pET guided by the ERA improve pregnant outcomes in good-prognosis patient population (GPP, 0–2 prior failed ETs) and recurrent implantation failure (RIF)/poor-prognosis patient cohort separately. The secondary objective was to estimate the prevalence of displaced WOI in above two infertile population.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent implantation failure (RIF) is defined as the failure of high quality embryos to implant after several ART cycles. The endometrial receptivity assay (ERA: Igenomix, Miami, FL) was an attempt to determine the optimal WOI by defining the transcriptomic signature for endometrial receptivity [8] . Such a test potentially provides a rational basis for evaluating and treating RIF [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The endometrial receptivity assay (ERA: Igenomix, Miami, FL) was an attempt to determine the optimal WOI by defining the transcriptomic signature for endometrial receptivity [8] . Such a test potentially provides a rational basis for evaluating and treating RIF [8][9][10] . The ERA was originally designed to evaluate the expression of 238 genes based on mRNA in tissue obtained from a timed endometrial biopsy taken 120 hours after the addition of progesterone in a woman with an estrogen primed endometrium.…”
Section: Introductionmentioning
confidence: 99%